2013
DOI: 10.1002/jbmr.2100
|View full text |Cite
|
Sign up to set email alerts
|

CLCN7 and TCIRG1 Mutations Differentially Affect Bone Matrix Mineralization in Osteopetrotic Individuals

Abstract: Osteopetrosis is an inherited disorder of impaired bone resorption, with the most commonly affected genes being CLCN7 and TCIRG1, encoding the Cl À /H þ exchanger CLC-7 and the a3 subunit of the vacuolar H þ -ATPase, respectively. We and others have previously shown that the disease is frequently accompanied by osteomalacia, and that this additional pathology is also found in Tcirg1-deficient oc/oc mice. The remaining question was whether osteoid enrichment is specifically associated with TCIRG1 inactivation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 45 publications
4
27
0
1
Order By: Relevance
“…In the gastric gland parietal cells, protons are released into the lumen where the gastric juice denatures and digests the protein content of the food. Gastric acidification is also essential for calcium uptake through the gastro-intestinal tract, the consequence of which in this form of the disease is, as already stated, a rickets-or osteomalacia-like phenotype that adds to the osteopetrotic phenotype (19,20).…”
Section: Recessive Osteopetrosesmentioning
confidence: 81%
See 1 more Smart Citation
“…In the gastric gland parietal cells, protons are released into the lumen where the gastric juice denatures and digests the protein content of the food. Gastric acidification is also essential for calcium uptake through the gastro-intestinal tract, the consequence of which in this form of the disease is, as already stated, a rickets-or osteomalacia-like phenotype that adds to the osteopetrotic phenotype (19,20).…”
Section: Recessive Osteopetrosesmentioning
confidence: 81%
“…Cognitive function is frequently normal except in recessive syndromes due to OSTM1 and, less frequently, to CLCN7 gene mutations which cause primary neurodegeneration due to lysosomal storage disease affecting various areas of the brain, including cerebral and cerebellar cortices, hippocampus and retina (16,17). Furthermore, in other forms (gene implicated TCIRG1), patients also display increase of gastric pH, which may limit calcium absorption and contribute to hypocalcemia (19)(20). Based on data in mice (21), a similar increase of gastric pH could be hypothesized in patients harboring SNX10 mutations.…”
Section: Recessive Osteopetrosesmentioning
confidence: 99%
“…As an example, in mammals there are 4 isoforms of the asubunit; ATP6V0a1 (a1) and ATP6V0a2 (a2) are ubiquitously expressed and are associated with subsets of housekeeping V-ATPases. ATP6V0a3 (also referred to as TCIRG1, Atp6i, TIRC7, and a3) is found at high levels in osteoclasts [20], microglia [21], gastric parietal cells [22], pancreatic beta cells [23], and perhaps a few other cell types and associates with a specialized subset of V-ATPases that perform nonhousekeeping functions. Osteoclasts, for instance, express a1, a2, and a3 [24].…”
Section: Structure and Enzymatic Function Of V-atpasesmentioning
confidence: 99%
“…Soon thereafter, it was shown that about half of the human patients that suffer from autosomal malignant osteopetrosis have mutations in the a3-subunit [27,104]. The a3-subunit is expressed at high levels in osteoclasts, in pancreatic beta cells, in microglia in the brain, in gastric parietal cells, and a few other cell types [21][22][23][105][106][107]. It was found in a variety of tissues in early screens, but it is not clear which cell types [106] it was derived from.…”
Section: A-subunitmentioning
confidence: 99%
See 1 more Smart Citation